Reciprocal Study of Theology and Linguistics in Uzbekistan - Anvarovich, Mavlonov Otabek; Nasimovich, Radjabov Nasir (International Journal of Psychosocial Rehabilitation, 2020)
Since the last century, as a result of the great progress in every field of science method for studying them cooperatively have emerged. In linguistics, internal “resources” have almost explored, and most of the existing languages and their fields are comparatively studied. By that means, it led to the necessity to study it jointly with other disciplines. In multidisciplinary relations commenced to study linguistics correlatively with other disciplines, including theology. Such studies play a significant role in translating, understanding the true essence of religions and interpret their sacred sources. The article provides a comprehensive overview of theolingustics that emerged from the reciprocal action of religious and linguistic research. In addition to the emergence and development of theolingustics as a direction in linguistics, the author draws attention to the fact that the history of such research in Uzbekistan goes back to the distant past.